Synthetic, Spectral and Antibacterial Studies onComplexes of Co(II), Ni(II) and Cu(II) with2,2'-Imino Bis-4,4'-Diphenylthiazole - Patel, R.K.; Purohit, K.M.; Patel, R.N. (Asian Journal of Chemistry, 2010)
A series of complexes of the type ML2X2´ where M = Co(II), Ni(II) and Cu(II), L = 2,2´-iminobis-4,4´-diphenyl thiazole and X = Cl–, Br–, NO3– and ClO–4, have been synthesized and characterized on the basis of elemental analysis, molecular weight measurements, molar conductance, room temperature, magnetic moment, infrared and electronic spectral data. Elemental analysis confirms the stereochemistry of the complexes. The complexes are monomeric and nonelectrolytic in nature. Magnetic moment values indicate paramagnetic nature of the complexes. IR spectra reveal the coordination of the ligands and anions. The electronic spectral data suggest octahedral geometry for the complexes. The complexes show feeble to moderate antibacterial and antifungal activities.